"Lovingly" objectifying the other?: a critical description of the role identity of the Dutch Reformed Church, in light of their relational dynamics with 'the other' in a multiracial and unjust South African society - Van Zijl, Albertus Johannes De Mist (University of the Free State, 2017)
The study forwards a social-psychological perspective on the notions of reconciliation and social cohesion. In this hermeneutic, the social identity approach in social-psychology together with the psychology of prosocial intergroup behaviour, is utilised to critically appraise the role identity of the Dutch Reformed Church (DRC) in a multiracial South Africa. In-group role identity is informed by the social identity and relational dynamics in a specific intergroup context: Who we are in our relationship with others. I argue that group role identity has a negative impact on reconciliation and social cohesion when a strong in-group social identity becomes salient, because it leads to objectification of the other in the context of intergroup helping. Objectification occurs when people are differentiated from the in-group self as the other and then become strategically subservient to satisfy an in-group need. This is an automatic consequence of strong social identities. This study aims to answer how does the relational dynamics, from a socio-psychological perspective on social identity and prosocial group behaviour, inform the contemporary role identity of Dutch Reformed Church congregations regarding their relationship with the racial other in a multiracial and unjust South African society? The study historically traces the development of a strong white Afrikaner Christian social identity as core to the role identity of the DRC and how such an identity affected the relationship with the racial other. Mission constitutes the relational parameters of intergroup helping the DRC chose to engage with the other. The study argues that the racial other was objectified by the DRC because the missional relationship was managed strategically to serve the needs of the white Christian Afrikaner in-group. A theological critique against a relational praxis of othering and objectification is discussed. Liberation-, Black Liberation- and Feminist theologies forward a reciprocal relationship of mutuality based on the Imago Dei concept and a Christology where Christ identifies with the poor and oppressed in the social margin. This is a critique of the psychological mechanisms inherent in strong social group identities by arguing for a strong superordinate identity of all being made in the image of God and a purposeful identification with those in the social margin as participation in the Missio Dei. From a social-psychological perspective it is clear that reconciliation and social cohesion will be severely hampered before the other is accepted as a self, in a relationship of mutuality. Psychologically speaking, acts of neighbourly love will always be suspect in the context of strong social identities. This study seriously questions the significance of the contemporary DRC role identity in furthering the notions of reconciliation and social cohesion in a racially divided society where Afrikaner social identity is under threat. The helping endeavours of DRC congregations may still be interpreted as strategic in satisfying in-group needs: Objectifying the racial other as an object for alleviating guilt or as an object of charity to manage group impression or as a means to justify the social status of having a special calling to educate the racial other.
Dissertation (M. (Reconciliation and Social Cohesion))--University of the Free State, 2017
Keywords: Reconciliation; Social cohesion; Social identity approach; Objectification; Dutch Reformed Church